Digesting development why Philippine industrialization hardly took off - Palma, Alexander Michael G. (Tri-College, University of the Philippines Diliman, 2016)
"Institutions played a major role in the introduction of policy instruments that reflect the industrialization strategies adopted in specific post-independence era. Immediately after the Philippines gained independence, industrialization figured out in a certain pronouncements of the government that were criticized by nationalists because these pronouncements redound to a continued dependence on the U.S. economy. Foreign influences reflected prominently in hallmark trade and investment agreements, as well as in development assistance and forms of economic aid. These influences also mirrored the pattern of development of institutions which persisted for several years after independence. The paper attempts to examine how these influences resulted to the progression of industrial structure from its early origins to present from. These influences are mirrored in the ideas, language, and measured in monetary terms. The hypothesis of this paper is to provide validity to the assertion that mechanisms necessary to have initialized industrialization remain to be lacking in institutions of post-independence period. The paper is an attempt to provide the measureable parameters that will support this assertion and greater reforms in many aspects of governance."--Author